The Rhizoctonia-Meloidogyne Disease Complex in Flue-cured Tobacco - Batten, C. K. (Society of Nematologists, 1971)
If Meloidogyne incognita preceded Rhizoctonia solani by 10 days or 21 days in roots of greenhouse-grown tobacco plants, root rot was more extensive than when the nematode and fungus were introduced either simultaneously or separately or when R. solani was added after artificial wounding. Histological examination of galled roots 72 days after inoculation with R. solani revealed extensive fungal colonization in the root-knot susceptible cultivar 'Dixie Bright 101' when M. incognita preceded R. solani by 21 days. R. solani, normally nonpathogenic on mature tobacco roots, may cause severe losses when present with well-established root-knot nematode infections.